Causal Relationship Between Transport Inflation with Oil Prices and Exchange Rates - Tacinur Akça (İktisat Politikası Araştırmaları Dergisi)
The aim of this study is to examine the effects of oil prices and exchange rates on the inflation of the transportation sector between the years 2010 and 2022. The Toda-Yamamoto and Breitung- Candelon frequency domain causality test were employed as the methodologies for analysis. The variables used in the analysis are: the transportation services price index, European Brent oil prices, and dollar rate. In terms of the TodaYamamoto test results, a unidirectional causality relationship was found from oil prices and dollar rates to transportation prices over time. In terms of the Breitung and Candelon test results, short, medium, and long-term effects, both temporary and permanent, were determined from both oil prices and dollar exchange rates to transportation prices. When the results are evaluated in general, increases in energy prices and exchange rates cause inflation in the transportation sector. Reducing energy consumption, which is an important cost factor in the production and consumption channel of transportation, will not only reduce imports, but also reduce the need for foreign currency, while reducing prices in the transportation sector.